Orchids of the Southern Cone (1830–2000) – Part II. The Philippi dynasty: Plantarum Novarum Chilensium and Catalogus Plantarum Chilensium - Ossenbach, Carlos (Universidad de Costa Rica, 2023)
Bernhard Eunom Philippi (1811–1852), his brother Rudolph Amandus Philippi (1808–1904), and the latter’s son Federico Philippi (1836–1910) must be considered the main actors in the history of the natural sciences in Chile between 1840 and 1910. While Bernhard was responsible for convincing the rest of his family to emigrate to Chile (and in fact, became the initiator of German immigration to southern Chile), Rudolph became the leading Figure in Chile’s scientific community, becoming the first director of the National Museum of Natural History, a post he held from 1853 to 1897. The description of many new orchid species in the series Plantarum novarum Chilensium (1856–1864) during this time is only one of his merits. His son Federico took over the direction of the Museum after his father’s retirement until he died in 1910. Catalogus plantarum Chilensium (1881) stands out among his numerous publications.